Casos importados de febre Chikungunya em São Paulo, Brasil – Vigilância laboratorial – 2014 - Silva Nogueira, Juliana; Yurika Maeda, Adriana; Bisordi, Ivani; Rocco, Iray Maria; Gisele da Silva, Fernanda; Pereira de Souza, Renato; Sequetin Cunha, Mariana; Lisieux Moraes Coimbra, Terezinha; Kisielius, Jonas José; Silveira, Vivian Regina; dos Santos Silva, Sarai Joaquim; Rodrigues Oliveira, Ana Lúcia; et al. (BEPA. Boletim Epidemiológico Paulista, 2014)